Anticancer Compounds from Fungi: Review - Dhurgham A. H. Alhasan; Hawraa F. H. AL-abed (Iraqi Journal of Cancer and Medical Genetics, 2021)
After cardiovascular disease, cancer represents an important one of the causative agents leading to mortality. Therefore, it is considered as a world major problem in, cancer defined as a disease when cells have uncontrolled abnormal proliferation and division. This disease can overcome immune responses leading to destroy other cells. Different chemotherapies are used for treating cancer but only a few have satisfied results. Gene or protein delivering drugs are used to destroy the cancer cells. Concerning anti-cancer agents, fungi play an important role in producing these agents. Taxol, obtained from Taxomyces andreanae, is a typical example of the fungal anti-cancer drugs that it is used for treating cancers of the breast and ovaries. Other fungi can produce the anti-cancer compounds which are Alternaria tenuissima, Aspergillus flavus, Aspergillus fumigatus, Aspergillus oryzae, Fusarium fujikuroi, Fusarium oxysporum, Fusarium graminearum, Penicillium expansum, Pyrenophora triticirepentis, Rhizoctonia solani, and Trichophyton rubrum. That can be mini-review summarized a topic related to the anti-cancer products are obtained from fungi.